2013
DOI: 10.1063/1.4827856
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transition and electrical transport properties of delafossite CuCr1−xMgxO2 (0 ≤ x ≤ 12%) films prepared by the sol-gel method: A composition dependence study

Abstract: Highly transparent CuCr1−xMgxO2 (0 ≤ x ≤ 12%) films were prepared on (001) sapphire substrates by sol-gel method. The microstructure, phonon modes, optical band gap, and electrical transport properties have been systematically discussed. It was found that Mg-doping improved the crystal quality and enhanced the (00l) preferred orientation. The spectral transmittance of films approaches about 70%–75% in the visible-near-infrared wavelength region. With increasing Mg-composition, the optical band gap first declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…For example, both direct and indirect band gaps are influenced by the content of Mg within the Mg/ CuCrO 2 . They decrease for concentrations of Mg up to 8% but an increasing is then observed for greater dopant content [181]. This was attributed to the band gap renormalization and Burstein-Moss effect induced by the dopant.…”
Section: Optical Propertiesmentioning
confidence: 91%
See 2 more Smart Citations
“…For example, both direct and indirect band gaps are influenced by the content of Mg within the Mg/ CuCrO 2 . They decrease for concentrations of Mg up to 8% but an increasing is then observed for greater dopant content [181]. This was attributed to the band gap renormalization and Burstein-Moss effect induced by the dopant.…”
Section: Optical Propertiesmentioning
confidence: 91%
“…In order to accelerate the synthesis, Kumar et al use the microwave heating, as it enhances solid-state reaction kinetics [178]. Another chemical method of fabrication for copper chromium delafossite is the sol-gel process [179][180][181][182][183][184][185][186]. Copper and chromium hydrate precursors are dissolved in alcoholic or water-based solutions.…”
Section: Deposition Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More important reason is that the overdoping Mg disturbs the up-spin Cr 3d orbitals, which greatly impedes the dispersion of the 3d states [10]. The less disperse electronic states decrease the effective transport and holds back the increase of the conductivity.…”
Section: Photoluminescence Emissionsmentioning
confidence: 99%
“…In our previous work, the sol-gel derived CuCr 1−x Mg x O 2 films have been proved to possess relatively high transmittance above 70% in the visible-near-infrared wavelength region. It has been found that the conductivity of CuCr 1−x Mg x O 2 increases with the temperature from 150 to 300 K. There is a transition of the carrier transport mechanism from a thermal activation behavior to a variable range hopping at a certain temperature [3,10]. Nevertheless, the origins of absorption behavior and electrical transport properties have not been clarified to date.…”
Section: Introductionmentioning
confidence: 95%